Use of a high‐fidelity simulator to develop testing of the technical performance of novice anaesthetists - Forrest, F. C.; Taylor, M. A.; Postlethwaite, K.; Aspinall, R. (British journal of anaesthesia : BJA, 2002)
Background. We used the Delphi technique to gain a consensus from 26 consultant anaesthetists about technical tasks during general anaesthesia. We then developed a technical scoring system to assess anaesthetists undertaking general anaesthesia with rapid sequence induction. Methods. We then followed the performance of six novice anaesthetists on five occasions during their first 3 months of training. At each, visit each novice ‘anaesthetized’ the Human Patient Simulator at Bristol Medical Simulator Centre. For comparison seven post‐fellowship anaesthetists were scored on one occasion. Results. Novice scores improved significantly over the 12‐week period (P<0.01). A significant difference was also found between the final novice scores and the post‐fellowship subjects (P<0.05). Conclusions. These findings suggest that simulation can be used to observe and quantify technical performance. Br J Anaesth 2002; 88: 338–44